Wood Carving In Selected Kelantan And Terengganu Timber House - Kamaruddin, Zumahiran (Journal of Architecture, Planning and Construction Management, 2020)
This study aimed to determine the significance and meanings of the carved components and their placements within the timber houses of Kelantan and Terengganu during the periods of 1800s to 1930s. An analytical review on 25 sets of measured drawings of 14 Kelantan houses and 11 Terengganu houses including a total of 148 carved components was conducted by visual descriptive and interpretative analyses. The analytical review of the drawings which were obtained from the Centre for the Study of Built Environment in the Malay World at the Department of Architecture in Universiti Teknologi Malaysia was embraced as a principal method of data collection. Semi-structured interviews with five prominent woodcarvers on art and crafts of wood carving were conducted to substantiate the findings from the analytical review. The woodcarvers’ interpretations were required for verification and validation. The results suggest that 17 types of carved components were found in the houses which were dominated by ventilation panels. A significant pattern of visual attributes was prevalent in the components including types of motifs, shapes and layouts, forms of incision and perforation, carving patterns and compositional principles. Motifs of flora, geometry, Arabic calligraphy and combination of these were depicted in two and three dimensional compositions either in relief or non-relief and perforated or non-perforated forms. Configurations of carving pattern, shapes and layouts of the components were in agreement with the nomenclature of their placements within the interior and exterior fabric and the different forms of the houses. Consistency in the distributions of the components suggests its functions for practical, aesthetical and socio-cultural values and signifies hierarchical utilization of spaces whilst strengthening the regional forms of the house architecture. These qualities including the visual attributes contribute to the significance and meanings of the carved components in the architecture of the selected Kelantan and Terengganu timber houses.